БЎЛАЖАК ЎҚИТУВЧИНИНГ АКМЕОЛОГИК МЕХАНИЗМЛАРИНИ РИВОЖЛАНТИРИШ - Даукеева, А. (SCIENCE and SOCIETY, 2022)
Acmeological competence of the future teacher’s development is defined as the unity of theoretical and practical training and the ability to professionally carry out professional activities.